Prescription and antibiotic resistance patterns at selected critical care units of the largest teaching and referral hospital in Kenya - Obegi, Emmah; Oluka, Margaret; Opanga, Sylvia; Aywak, Dorothy; Okalebo, Faith; Okumu, Mitchel (Frontiers in Tropical Diseases, 2025)
BackgroundLittle is known about the prescription and antibiotic resistance patterns at Kenyatta National Hospital (KNH)’ s critical care units (CCUs). The present study aimed to evaluate these patterns at selected CCUs at KNH.MethodsThis was a descriptive, retrospective cross-sectional study of selected CCUs at KNH between January and December 2017. Data on prescription and antibiotic resistance patterns were abstracted from the medical records of patients ≥13 years old admitted at selected CCUs at KNH during the study period.Results309 patients with a mean age of 40.6 ±17.5 years were recruited; trauma was the leading cause of admission (72/309, 23.53%), and most were male (n=158, 51.1%). Antibiotic therapy was initiated before CCU admission in 304/309 (98.4%) of the patients, documentation of antibiotic indications was low for both empirical (25%) and targeted therapy (41.6%), and ceftriaxone (36.8%), metronidazole (16.9%), and meropenem (12.4%) were predominantly prescribed. Pre-therapy cultures were obtained in 51.1% of cases, with 42.7% yielding positive results and Klebsiella pneumonia (23.9%), Acinetobacter baumanii (16.4%), and Escherichia coli (10.5%) predominating. Furthermore, 67% (n=11) of K. pneumonia isolates were sensitive to meropenem, 82% (n=9) of Acinetobacter baumanii isolates were sensitive to amikacin, 55% (n=6) to meropenem and 27% (n=3) were sensitive to ceftazidime and cefepime. All the A. baumanii isolates were resistant to tigecycline, linezolid, and teicoplanin. Most (86%, n=6) of the E. coli isolates were sensitive to meropenem, 71% (n=5) were sensitive to amikacin, and 43% (n=3) were sensitive to gentamicin.ConclusionsThe high rates of pre-CCU antibiotic initiation, low documentation of therapeutic indications, and widespread resistance to commonly used antibiotics at the Kenyatta National Hospital highlight the urgent need for improved antimicrobial stewardship programs. Moreover, the predominance of multi-drug resistant organisms, particularly K. pneumonia and A. baumanii, and their variable sensitivity patterns to reserve antibiotics like meropenem suggests there is need for regular surveillance and update of antibiotic guidelines.